An Experimental Investigation of New Hybrid Composite Material using Hemp and Jute Fibres and Its Mechanical Properties through Finite Element Method". (2018) - Sowmya, C.; Ramesh, V.; Karibasavaraja, D.
Abstract: This paper discusses the development of new hybrid composite using natural fibre as reinforcement with commercially available epoxy resin and polyester resins with the hybrid materials. Jute, hemp fiber and epoxy resin and polyester resin along with graphite filler were developed for 30°, 45° and 90° fibre orientations. The experimentation done on Hemp/Polyester, Hemp/Epoxy, 0/90° Hybrid/polyester, 0/90° Hybrid/Epoxy, 0/30° polyester, 0/30° Epoxy, 0/45° Polyester and 0/45° Epoxy. Thus fabricated materials were subjected to tensile, flexural, impact, Specific gravity,  water test and hardness tests at different orientations. In addition, the effect of combination of two fibers was also investigated. The finite element analysis was carried out to compare it with experimental results. The conclusions were drawn as regards to identifying the effects of these hybrid composites on varying material properties.